Relación entre asimetría fluctuante y el tratamiento hormonal, cirugía-ortodoncia maxilofacial, traumatismos y malformaciones craneofaciales (2018)
ABSTRACT: In this work we test for the putative association between facial fluctuating asymmetry (FFA) and hormone treatments, maxillofacial surgery, orthodontics, injuries, and malformations. A protocol of five photographs and photogrammetric reconstruction was implemented to place thirty-four 3D landmarks in 3162 individuals aged between 18 and 85 years, belonging to the CANDELA initiative. A Procrustes ANOVA test was used to obtain individual facial fluctuating asymmetry scores. One way ANOVA, Welch, and Levene tests were conducted to explore the potential differences between mean and variance of the response variables. Our results indicate that women who received some hormonal treatment showed higher fluctuating facial asymmetry scores in relation to the unaffected group, this being persistent once the effects of heterozygosity (genetic ancestry) and further variables had been statistically controlled. The shape changes corresponding to this association are focused on the chin, jaw, lower lip, prefrontal region, nose, and ears. Previous reports suggested a potential relationship between facial asymmetry and hormone levels, but to the best of our knowledge there are no reports indicating the causation underlying the association detected here. This report is one more evidence of the association between hormone intake and facial asymmetric features in urban admixed Latin American populations.